Coastal Cryohydrogeological Model - Julia A. Guimond (Hydroshare, 2021)
This resource includes a newly developed coastal cryohydrogeological model that simultaneously solves the coupled partial differential equations describing variable-density fluid flow and solute transport, and heat transfer with salinity-dependent freeze-thaw. This code was developed using the commercial code FlexPDE. Included in this resource are the scripts and initial condition files necessary to run various sea-level rise and warming scenarios for three values of intrinsic permeability.